2007
DOI: 10.1111/j.1547-5069.2007.00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomics for Health in Preconception and Prenatal Periods

Abstract: Research, education, advocacy, and anticipatory guidance are needed as women and families obtain more genetic and genomic information before and during pregnancy. All nurses will be involved in helping patients use genetic and genomic information to understand risk and to develop strategies to modify risk, and in translating the expanding array of genomic information to improve birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Optimal health before pregnancy includes having a reproductive plan, having a healthy weight, folic acid intake, exercising, healthy nutrition, and abstaining from tobacco and alcohol use [8][9][10][11]. One study that reported on folate levels during the preconception period (folate levels are associated with preventing neural tube defects very early in pregnancy before a woman may even know she is pregnant), found adequate folate levels for Mexican-American and non-Hispanic White women, but not for non-Hispanic Black women [12].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal health before pregnancy includes having a reproductive plan, having a healthy weight, folic acid intake, exercising, healthy nutrition, and abstaining from tobacco and alcohol use [8][9][10][11]. One study that reported on folate levels during the preconception period (folate levels are associated with preventing neural tube defects very early in pregnancy before a woman may even know she is pregnant), found adequate folate levels for Mexican-American and non-Hispanic White women, but not for non-Hispanic Black women [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies are needed to determine if such a strategy might decrease preterm birth rates as well. Perhaps as we learn more about the differing susceptibility to neural tube defects or preterm birth that varying MTHFR alleles represent, we will be able to use genetic testing to identify susceptibility and provide the basis for personalized preventive recommendations (Dolan et al, 2007a). Similar approaches may become available to identify susceptibility to other common environmental risk factors, such as smoking and infection, that will enhance our ability to provide individualized preconception and prenatal recommendations.…”
Section: Genomic Research: Increasing Understandingmentioning
confidence: 97%
“…Since the mapping and sequencing of the human genome was completed in 2003, 1 an immense amount of genetic and genomic information has been discovered. The use of genetics and genomics in the clinical care of pregnant women may expand the diagnosis, treatment, and prevention of human diseases and complications such as preterm birth, preeclampsia, gestational diabetes, multifactorial birth defects, and rare single‐gene disorders 2 . The clinical application of genetic and genomic advances has the potential to transform preconception and pregnancy care and improve pregnancy outcomes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of genetics and genomics in the clinical care of pregnant women may expand the diagnosis, treatment, and prevention of human diseases and complications such as preterm birth, preeclampsia, gestational diabetes, multifactorial birth defects, and rare single‐gene disorders 2 . The clinical application of genetic and genomic advances has the potential to transform preconception and pregnancy care and improve pregnancy outcomes 2 . Midwives are in a key position to use genetic and genomic information, with the goal of improved maternal and neonatal health 3 …”
Section: Introductionmentioning
confidence: 99%